The Hero-Leader Matrix in Business and Cinema - Fournout, Olivier (Journal of business ethics, 2017)
Textbooks and manuals on management suggest that managers are heroes who deal with difficult problems of collective adaptation and change. American films are similarly built on the premise of a hero confronted with extremely difficult situations. What if this hero figure promoted for so long in both management literature and the American film industry was the same at the structural level? This paper will attempt to clearly define the ethical performance of heroes that is perhaps shared by the imagination industry (hollywood) and the workplace on the long run. We shall follow this picture of a hero-leader in the ethics of business and cinema through a large corpus of movies and writings on management and provide a set of six features for examining both, a common heroic structure we shall call the Hero-Leader Matrix.